Banks Versus Bonds: the Emergence and Persistence of Two Financial Systems - Sandeep Baliga; Ben Polak (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
We use a simple graphical moral hazard model to compare monitored (non-traded) bank loans versus traded (non-monitored) bonds as sources of external funds for industry. We contrast the conditions that theoretically favour each system, such as the size and number of firms, with conditions prevailing when these financial systems evolved during the British and German industrial revolutions. Then, to address why different systems have persisted, we consider a larger model with entry so that firm size and number are endogenous. We show that multiple equilibria can exist if financiers take the industrial structure as given and vice versa, and we compare these equilibria in welfare terms. Finally, we argue that with, if bilateral co-ordination is possible, Anglo-Saxon style finance systems can only persist if they are efficient, but an economy can get stuck in an inefficient German style system.
Keywords: 330